Pay dispersion among the top management team and outside directors: Its impact on firm risk and firm performance - Patel, Pankaj C.; Li, Mingxiang; del Carmen Triana, María; Park, Haemin Dennis (Human Resource Management, 2018)
Two key groups central to improving firm performance are the top management team (TMT) and the board of directors. Executives undertake strategic actions, whereas board members fulfill their resource provision and monitoring roles. Drawing on tournament theory and equity theory, we propose that high pay dispersion among outside directors and the TMT is positively associated with strategic risk, whereas high (low) TMT pay dispersion and low (high) outside director pay dispersion are positively associated with firm performance. Our predictor is the unexplained component of horizontal pay dispersion, or the residual of pay dispersion resulting from regressing pay on observable firm, industry, period, and individual characteristics. Our results highlight the importance of unexplained pay dispersion for TMTs, but not for boards of directors, in improving firm performance.